Spondylitis and Arthritis in Familial Mediterranean Fever - Selda SARIKAYA,; Şenay ÖZDOLAP,; Erdem MARAŞLI, (Archives of Rheumatology, 2012)
Objectives: This study aims to evaluate the clinical features of patients who are diagnosed with familial Mediterranean fever (FMF) and followed due to arthritis/spondylitis findings. Patients and methods: The data of 29 patients (12 males, 17 females; mean age 26.1±11.2 years; range 16 to 51 years) who presented with arthritis and/or inflammatory spinal pain and were diagnosed with FMF between November 2000 and March 2012 were retrospectively analyzed. The age and gender of the patients were recorded. The age of onset of arthritis/spondylitis, age at FMF diagnosis, family history of FMF, and previous surgical history as well as the number of affected joints and their localization were also recorded. The presence of peripheral arthritis in patients with sacroiliitis and spondylitis was also investigated, and the drugs used for treatment were recorded. The results were documented in patients who underwent human leukocyte antigen (HLA)-B27 and Mediterranean fever (MEFV) gene analysis. Results: The mean age of onset of arthritis/spondylitis was 20.4±9.1 years. Arthritis was observed in 24 of the patients (monoathritis in 15 patients, oligoarthritis in 9 patients), and the most affected peripheral joint was the ankle (n=13). Five patients had both arthritis and spondylitis while five others had only spondylitis. Four patients had a history of total hip replacement, one with knee debridement, and one with an appendectomy. The Mediterranean fever gene analysis was performed on 27 patients, and 10 of them (37%) had a M694V homozygous mutation, and those who had undergone total hip replacement had the same mutation. The HLA-B27 gene analysis was performed on 21 patients, and two of them tested positive. Conclusion: Familial Mediterranean fever should be included in the differential diagnosis of inflammatory arthritis and spondylitis in young patients. Classical arthritis attacks are the most common clinical presentation; however, chronic erosive joint involvement and spondylitis should be also recognized as clinical features of the disease. Although colchicine therapy is effective in preventing attacks and amyloidosis, both disease-modifying antirheumatic drugs (DMARDs) and biological drugs appear to be effective in treating severe forms of rheumatological disorders and chronic erosive arthritis.